A Comparative Analysis of Theoretical Models of Gravity Movements of Cohesionless Granular Media - SZCZEPIŃSKI, W. (Engineering Transactions, 2007)
Three different theoretical models for the analysis of movements of granular media caused by the gravity forces only are critically discused. In each of them the motion is treated as a purely kinematical problem. It has been shown that in application to varoius practical problems, they lead to different displacements patterns (e.g. funnel or mass flow, formation of shear bands or a flow without such bands). Examples of applicaion illustrate the discussion.